The Outline of Communal ‘Ars Moriendi’ in Egalitarian Transhumanism - Polowczyk, Łukasz Paweł (Adam Mickiewicz University in Poznań, Faculty of Philosophy, 2022)
This paper outlines the proposal for an egalitarian, transhumanist, and communal version of ars moriendi that should be coherent and meet the consequentialist criteria of the principle of minimizing anti-values and maximizing values, especially the ethical values of freedom and happiness. Transhuman-ist augmented dying (AD) refers to the extended body-mind, free from harmful religious and political ideologies. At present, a feasible art of dying can be systematically supported by anesthetics and psy-chedelics (entheogens), computer games, virtual reality, and good death machines. Its egalitarian form requires a deeply democratic society, and its progress may need a transition to a type 1 society on the Kardashev scale.
Keywords: Transhumanism; ars moriendi; egalitarianism; psychedelics; happiness; the ideology of dying; the extended body-mind